The Brief Fatigue Inventory is reliable and valid for the burn patient cohort. Issue 5 (August 2015) - Toh, Christopher; Li, Marie; Finlay, Vidya; Jackson, Teresa; Burrows, Sally; Wood, Fiona M.; Edgar, Dale W.
Highlights: Large cohort study to determine a measure of fatigue levels after burn. Brief Fatigue Index is a reliable and valid measure of fatigue in burn patients. Fatigue levels are greater in major burns and in females. Abstract: Objective : After burn, patients are at risk of fatigue which may influence negatively their capacity to participate in activity, rehabilitation and other treatments. Fatigue may stem from the wound healing and systemic responses to burn which drive a hypermetabolic state that may persist for months. However, an established method is not available for objectively measuring fatigue after burns. The Brief Fatigue Inventory (BFI) was hypothesised to be an appropriate option for assessments following severe burn. The primary aim of the study was to establish if the BFI was reliable and valid in a burn patient sample. Methods : Adult patients admitted between 2009 and 2013 to Royal Perth Hospital Burn Center were included. Patients completed the BFI and Burns Specific Health Scale Brief (BSHS-B) in tandem at one, three, six and 12 months after burn. Reliability was assessed using Cronbach's alpha; construct validity using factor analysis and multi-variable regression of BFI; and, criterion validity with longitudinal regression of BFI with BSHS-B. Results : The sample ( n  = 587) had a median TBSA of 3% (range = <1–75%). The BFI demonstrated excellent reliability ( α  > 0.90). The factor analysis confirmed a single-domain construct, centred around the first scale item. Good correlation between BFI and BSHS-B scores ( p  < 0.001) on longitudinal analysis confirmed criterion validity. There was a significant difference in fatigue scores between minor and major burn patients and a significant association of fatigue levels over time with TBSA. Conclusion : The BFI is a reliable and valid tool for fatigue measurement in patients during the first 12 months after burn.